ProBDNF promotes sepsis-associated encephalopathy in mice by dampening the immune activity of meningeal CD4+ T cells - Luo, Ru-Yi; Luo, Cong; Zhong, Feng; Shen, Wei-Yun; Li, Hui; Hu, Zhao-Lan; Dai, Ru-Ping (Journal of neuroinflammation, 2020)
Sepsis-associated encephalopathy (SAE) increases the mortality of septic patients, but its mechanism remains unclear. The present study aimed to investigate the roles of T lymphocytes, proBDNF, and their interaction in the pathogenesis of SAE. Fear conditioning tests were conducted for cognitive assessment in the lipopolysaccharide (LPS, 5 mg kg )-induced septic mice. Meninges and peripheral blood were harvested for flow cytometry or qPCR. FTY720 and monoclonal anti-proBDNF antibody (McAb-proB) were used to investigate the effect of lymphocyte depletion and blocking proBDNF on the impaired cognitive functions in the septic mice. In the septic mice, cognitive function was impaired, the percentage of CD4 T cells were decreased in the meninges (P = 0.0021) and circulation (P = 0.0222), and pro-inflammatory cytokines were upregulated, but the anti-inflammatory cytokines interleukin (IL)-4 (P < 0.0001) and IL-13 (P = 0.0350) were downregulated in the meninges. Lymphocyte depletion by intragastrically treated FTY720 (1 mg kg ) for 1 week ameliorated LPS-induced learning deficit. In addition, proBDNF was increased in the meningeal (P = 0.0042) and peripheral (P = 0.0090) CD4 T cells. Intraperitoneal injection of McAb-proB (100 μg) before LPS treatment significantly alleviated cognitive dysfunction, inhibited the downregulation of meningeal (P = 0.0264) and peripheral (P = 0.0080) CD4 T cells, and normalized the gene expression of cytokines in the meninges. However, intra-cerebroventricular McAb-proB injection (1 μg) did not have such effect. Finally, exogenous proBDNF downregulated the percentage of CD4 T cells in cultured splenocytes from septic mice (P = 0.0021). Upregulated proBDNF in immune system promoted the pathogenesis of SAE through downregulating the circulating CD4 T cells, limiting its infiltration into the meninges and perturbing the meningeal pro-/anti-inflammatory homeostasis.